Effect of vegetarian diets on renal function in patients with chronic kidney disease under non-dialysis treatment: A scoping review - Valim,Agnes (2022)
Abstract Vegetable protein diets (VPDs) in chronic kidney disease (CKD) patients may be related to beneficial biological actions and possibly clinical impact. This is a scoping review that merge studies that evaluated the effect of a vegetarian diet on kidney function in adults with CKD under non-dialysis treatment. The evaluated outcome was the impact in renal function assessed by eGFR or creatinine clearance. MEDLINE (accessed by PubMed) was searched up to September 8, 2020. Data were extracted by two independent reviewers, who also assessed the quality of the studies. Of 341 retrieved articles, 4 studies assessing 324 patients were included in the analysis. One study showed that a very low-protein ketoanalogue-supplemented vegetarian diet had benefits in relation to a conventional low-protein diet, while the other three studies demonstrated no difference in kidney function between the evaluated diets. Additional studies are needed to assess the benefits of vegetarian diets for further recommendations in CKD management.